2009
DOI: 10.1111/j.1745-4557.2009.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Honey Shelf Life

Abstract: Fourteen commercial honey samples of different botanical origin (acacia, chestnut, citrus, eucalyptus, multifloral) were stored for up to 18 months at room temperature. Both 5‐hydroxymethylfurfural (HMF) and diastase were evaluated and kinetics carried out. The highest HMF increase was in citrus and eucalyptus honeys at 3 mg/kg/month; the lowest in chestnut at 0.256 mg/kg/month. The highest diastase deactivation was in eucalyptus honey at 0.485 DU/kg/month; the lowest was in chestnut at 0.258 DU/kg/month. Hone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…In this study, the moisture values were between 14.86±0.066% (chaste tree natural-3) and 19.9±0.066% (pine honey commercial-1). These results were like the some of the studies reported (4,(43)(44)(45)(46)(47). Belitz et al (48) offered 17.1% of moisture gradient as a threshold value for the fermentation of honey.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the moisture values were between 14.86±0.066% (chaste tree natural-3) and 19.9±0.066% (pine honey commercial-1). These results were like the some of the studies reported (4,(43)(44)(45)(46)(47). Belitz et al (48) offered 17.1% of moisture gradient as a threshold value for the fermentation of honey.…”
Section: Resultssupporting
confidence: 91%
“…Table 8 and 9 show the kinetic constants of HMF formation and diastase deactivation during storage. (4). In general, the chaste tree honeys had the higher rate of diastase deactivation than the pine honeys during storage at room temperature.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The degradation of 3‐DG leads to the formation of several compounds, the most well known of which is 5‐hydroxymethylfurfural (HMF) (Belitz and others 2009), the most commonly used quality index to measure aging and/or overheating in honey (Zappalà and others 2005). Its content in honey varies depending on, above all, pH and florality, rather than heat treatments and/or storage conditions (Sing and Bath 1998; Tosi and others 2002; Fallico and others 2004, 2009; Zappalà and others 2005). Thus, an interesting approach to assess the quality of honey would be to measure the presence of 1,2‐dicarbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…HMF is an important quality criterion formed as a result of dehydration of hexose in honey in an acidic environment and it varies depending on chemical characteristics of honey, like sugar, pH, total acidity, honey processing, and storage temperature (6,10,12,15). According to the above mentioned TFC on Turkish honey, HMF value is limited to be maximum 40 mg/kg in flower honey and honeydew honey products (16).…”
Section: Introductionmentioning
confidence: 99%